Exploring the Impact of Player Traits on the Leaderboard Experience in a Digital Maths Game - André Almo; Mariana Rocha; Attracta Brennan; Pierpaolo Dondio (Serious Games Society, 2024)
Digital Game-Based Learning (DGBL) uses digital games to enhance engagement and learning, but its efficacy is linked to game features. Leaderboards are a commonly used feature to increase motivation through competition, improving engagement and learning outcomes. However, infinite leaderboards, displaying all players in an ordered ranking based on their scores, can demotivate players depending on their performance and characteristics. This study investigated primary school students' experience with an infinite leaderboard during a digital maths game intervention. 1389 Irish students participated in a 6-week programme with the game 'Seven Spells,' which featured an infinite leaderboard. Player traits and opinions about the game and its leaderboard were gathered via questionnaires and surveys. Leaderboard enjoyment was influenced by players' position on the leaderboard and maths anxiety levels. Maths anxious players disliked the leaderboard more than non-anxious players, even after controlling for their position on the leaderboard. How much players liked to play against each other was also found to be a significant factor predicting the enjoyment of the leaderboard. There was also a small correlation between leaderboard enjoyment and overall game enjoyment. These insights exemplify players' characteristics that should be considered when incorporating infinite leaderboards into maths games to avoid negative impacts on gaming experiences.